2004
DOI: 10.1073/pnas.0308334100
|View full text |Cite
|
Sign up to set email alerts
|

The role of Shc and insulin-like growth factor 1 receptor in mediating the translocation of estrogen receptor α to the plasma membrane

Abstract: Our previous studies demonstrated that 17␤-estradiol (E2) rapidly induces the interaction of estrogen receptor ␣ (ER␣) with the adapter protein Shc, the translocation of ER␣ to the cell membrane, and the formation of dynamic membrane structures in MCF-7 breast cancer cells. The present study examined how E2 causes ER␣ to translocate to the region of the plasma membrane and focused on mechanisms whereby Shc and the insulin-like growth factor-1 receptor (IGF-1R) mediate this process. Shc physically interacts wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
271
1
8

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 318 publications
(291 citation statements)
references
References 37 publications
(31 reference statements)
11
271
1
8
Order By: Relevance
“…The mER has no intrinsic transmembrane domain, raising the question of how it binds to the plasma membrane. The mER from a cytoplasmic pool may translocate to the inner face of the plasma membrane and tether to it through proteins, such as caveolin-1 or growth factor receptors, possibly via palmitoylation (Acconcia et al, 2005a;Razandi et al, 2002;Song et al, 2004). Caveolin- Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mER has no intrinsic transmembrane domain, raising the question of how it binds to the plasma membrane. The mER from a cytoplasmic pool may translocate to the inner face of the plasma membrane and tether to it through proteins, such as caveolin-1 or growth factor receptors, possibly via palmitoylation (Acconcia et al, 2005a;Razandi et al, 2002;Song et al, 2004). Caveolin- Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Using antibodies directed against different epitopes of nuclear ER, many laboratories have demonstrated that some forms of ER can locate in the region of the cell membrane (Razandi et al, 2003;Simoncini et al, 2003;Song et al, 2004). Toran-Allerand et al (2002) described a novel mER, designated ER-X, which is enriched in the brain, uterus, and lung of the postnatal rodent and prefers 17a-estradiol to 17b-estradiol as the ligand.…”
Section: Introductionmentioning
confidence: 99%
“…Effector molecules such as SHC-transforming protein 1, Akt, and MAPK are activated by adaptor protein Src and PI3K [62,63]. The crosstalk between E2 and other growth factor signals suggests that adaptor proteins are essential for extranuclear actions of ERα.…”
Section: E2 Signaling In Breast Carcinogenesismentioning
confidence: 99%
“…28 A series of studies by other investigators suggested that ERα and the IGF-1 receptor might interact. 28 We tested the model that estradiol caused binding of SHC to ERα but also caused phosphorylation of the IGF-1 receptor. In this way, SHCwould serve as the "glue" which would tether ER alpha to the plasma membrane where it would bind to the SHC acceptor site.…”
Section: Phenomenon Of Hypersensitivity: Mechanisms and Pathwaysmentioning
confidence: 99%